Analisis Penilaian Pengetahuan dalam Materi Diagram Batang Menggunakan Media Visual pada Siswa Kelas IV SDN Sewan Kebon 1 - Morningrum, Roro Dewila; Aryanih, Eka; Magdalena, Ina; Septianih, Nabilah; Oktavia, Dela (Lembaga Yasin AlSys, 2023)
This study aims to analyze the assessment of knowledge in bar chart material using visual media in fourth grade students of SDN Sewan Kebon 1. Regarding knowledge in bar chart material there are many obstacles that are still not understood by grade IV students, especially in determining the x axis and y axis, difficulties determine the object in the process and how to determine the amount in a bar chart, grade IV students also do not understand how to determine the difference between the largest and smallest data. Therefore, the solution to overcome these obstacles is by using visual media because it can attract students' understanding to make it easier to understand the bar chart material. This type of research used is qualitative research with descriptive methods. Data collection techniques in the form of observation, interviews, documentation and tests. The research subjects were class IV teachers. The results obtained in this research are that students reach 100 and the lowest score is 60, this is important for students to increase their scores. In the assessment the teacher gives the appropriate value.